Insulin resistance in cerebral small vessel disease: a mini review - Su, Chen; Cui, Zhigang; Guo, Junhong (Frontiers in Neuroscience, 2026)
Cerebral small vessel disease (CSVD) is a leading cause of stroke and vascular cognitive impairment, but its metabolic determinants are not fully understood. Emerging evidence indicates that insulin resistance (IR) plays a crucial role in CSVD through vascular, inflammatory, and oxidative mechanisms. Higher IR levels may be associated with greater burdens of white matter hyperintensities, lacunes, cerebral microbleeds, and enlarged perivascular spaces. Mechanistic studies suggest that IR impairs endothelial nitric oxide signaling, disrupts the blood–brain barrier, promotes vascular remodeling, and alters astrocytic aquaporin-4 polarization, which together aggravate both ischemic and hemorrhagic microvascular injury. Clinically, IR represents a modifiable target, and interventions that reduce IR, including the use of pioglitazone, metformin, glucagon-like peptide-1 receptor agonists, physical activity, and dietary modification, may help slow CSVD progression. This mini review summarizes current epidemiological and mechanistic evidence linking IR to CSVD and highlights the potential of metabolic regulation as a strategy to prevent or mitigate small-vessel–related brain injury.